Hotspots and future directions in rheumatoid arthritis-related cardiovascular disease: A scientometric and visualization study from 2001 to 2021 based on Web of Science - Wen, Pengfei; Luo, Pan; Zhang, Binfei; Wang, Yakang; Hao, Linjie; Wang, Jun; Guo, Jianbin; Liu, Rui; Zhang, Yumin; Chen, Juan (Frontiers in Medicine, 2022)
Background: The morbidity and mortality of cardiovascular diseases (CVD) in patients with rheumatoid arthritis (RA) is significantly higher than those in the general population, leading to RA-related CVD has attracted broad attention and numerous articles have been published. However, no study has systematically examined this area from a scientometric perspective. This study aimed to visualize the knowledge structure and identify emerging research trends and potential hotspots in this field. Methods: Articles and reviews on RA-CVD published from 2001 to 2021 were extracted from the Web of Science Core Collection database. CiteSpace and VOSviewer software were used to visualize the knowledge network of countries, institutions, authors, references and keywords in this field. SPSS and Microsoft Excel software were used for curve fitting and correlation analysis. Results: A total of 2,618 articles and reviews were included. The number of publications about RA-related CVD significantly increased yearly. Publications were mainly concentrated in North America, Europe and East Asia. The USA contributed most with 699 publications, followed by the United Kingdom and Italy. Gross Domestic Product was an important factor affecting scientific output. University of Manchester and Professor Kitas George D. were the most prolific institutions and influential authors, respectively. Journal of Rheumatology was the most productive journal for RA-related CVD research. The research hotspots switched in the order of clinical features (cardiovascular events), mechanism exploration, anti-tumor necrosis factor therapy, risk factors, and antirheumatic drug safety, which can be observed from the keyword analysis and co-cited reference cluster analysis. Conclusions: This study found that research on RA-related CVD is flourishing. The safety and cardiovascular pharmacological mechanisms of anti-rheumatoid drugs, especially targeted synthetic DMARDs, would be the focus of current research and developmental trends in future research.